Self-Reported Awareness of Retinopathy Severity in Diabetic Patients [Erratum] - Qaseem Y (Dove Medical Press, 2020)
Qaseem Y, Samra S, German O, Gray E, Gill MK. Clin Ophthalmol. 2020;14:2855—2863. The authors have advised that there are several errors in the published paper which were introduced by the Editorial staff during the publication process. Page 2855, Abstract, Conclusion, the sentence “This consistent underestimation of severity across all a significant barrier to timely follow-up and treatment necessary to prevent future visual impairment” should read “This consistent underestimation of severity across all groups with DR may represent a significant barrier to timely follow-up and treatment necessary to prevent future visual impairment”. Page 2858, Table 2, notes section, the text “Notes: Each cell represents the number of patients with each combination of perceived versus actual DR severity. Underestimators are shaded in dark gray, accurate patients are shaded in light gray, and overestimators are shaded in white” should read “Note: Each cell represents the number of patients with each combination of perceived versus actual DR severity”. Page 2859, Figure 1, the note section was removed. The correct figure caption and note section is shown below.    Figure 1 Bar graphs representing the perceived severity of diabetic retinopathy (DR) in patients with no DR (A), mild/moderate DR (B), and severe DR (C). Note: Underestimators are shaded in dark gray, accurate patients are shaded in light gray, and overestimators are shaded in white. Read the original article